Tyrosine phosphorylation directs TACE into extracellular vesicles via unconventional secretion - Zhao, Zhe; Kesti, Tapio; Ugurlu, Hasan; Baur, Andreas; Fagerlund, Riku; Saksela, Kalle (Traffic, 2019)
When studying how HIV-1 Nef can promote packaging of the proinflammatory transmembrane protease TACE (tumor necrosis factor-alpha converting enzyme) into extracellular vesicles (EVs) we have revealed a novel tyrosine kinase-regulated unconventional protein secretion (UPS) pathway for TACE. When TACE was expressed without its trafficking cofactor iRhom allosteric Hck activation by Nef triggered translocation of TACE into EVs. This process was insensitive to blocking of classical secretion by inhibiting endoplasmic reticulum (ER) to Golgi transport, and involved a distinct form of TACE devoid of normal glycosylation and incompletely processed for prodomain removal. Like most other examples of UPS this process was Golgi reassembly stacking protein (GRASP)-dependent but was not associated with ER stress. These data indicate that Hck-activated UPS provides an alternative pathway for TACE secretion that can bypass iRhom-dependent ER to Golgi transfer, and suggest that tyrosine phosphorylation might have a more general role in regulating UPS.
CRIS-Team WoS Importer:2019-03-06